An Assessment of the Effectiveness of public Participation in the Legislative Process in Tanzania: A Case of the Cybercrimes Act No. 14 of 2015 - Godfrey Taisamo (International Journal For Multidisciplinary Research, 2026)
The enactment of the Cybercrimes Act No. 14 of 2015 of Tanzania witnessed outcries from various individuals, non-governmental organisations and human rights advocacy groups, in that its provisions were in violation of human rights and the Constitution as well. They associated the problem with the statute’s legislating process that it proceeded without sufficient regard to the constitutional tenet of public participation, which has been the case with so many statutes when enacted. The problem is further associated with lack of legislation on public participation as is seen in other jurisdictions. This paper argues that pre-legislative scrutiny is what gives legislation its legitimacy. It explores the concept of public participation in the legislative process of Tanzania, with a specific reference to the legislative process of the Cybercrimes Act of Tanzania of 2015, as evidence of non-adherence to the constitutional tenet of public participation in the legislative process of Tanzania. The omission is an infringement of guaranteed constitutional rights, thereby calling for legislation on public participation as well as intense and thorough review of the Cybercrimes Act of 2015, so as to enhance the rule of law and good governance, as recommended in this paper.